2023
DOI: 10.3390/app13148136
|View full text |Cite
|
Sign up to set email alerts
|

Sound Wave Absorption Coefficient and Sound Velocity in Thermally Modified Wood

Abstract: The present work analyses the absorption coefficient of sound waves and the speed of sound propagation in thermally modified wood. The high resistance to weathering, fungi, and better dimensional stability, and therefore the broad physical properties of this material, are well known. However, the literature lacks numerous analyses of its acoustic characteristics. During the study, high-density species, such as oak, red oak, and beech were used, in contrast to pine. Pine wood during this test was characterised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Previous studies on the sound absorption properties of natural wood-based materials include Wassilieff [17], who demonstrated that the sound absorption performance of wood fibers and chips can be rationally described using three parameters based on Rayleigh's model: flow resistivity, porosity, and tortuosity. Mania et al [18] measured changes in sound absorption rates after heat treatment of various types of wood at high temperatures. Chojnacki et al [19] designed acoustic panels that absorb sound over a wide frequency range by investigating curved shapes and hole-drilling methods applied to the wood surface.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the sound absorption properties of natural wood-based materials include Wassilieff [17], who demonstrated that the sound absorption performance of wood fibers and chips can be rationally described using three parameters based on Rayleigh's model: flow resistivity, porosity, and tortuosity. Mania et al [18] measured changes in sound absorption rates after heat treatment of various types of wood at high temperatures. Chojnacki et al [19] designed acoustic panels that absorb sound over a wide frequency range by investigating curved shapes and hole-drilling methods applied to the wood surface.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists Kellogg and Wangaarl (1969) and Mania et al (2023) have frequently observed a connection between the quantity of sound absorption coefficient and the porosity of wood and charcoal. The porosity (C) of the wood has been determined using the formula:…”
Section: Fig 24 Charcoal Samples After Carbonisation (Made By the Aut...mentioning
confidence: 99%
“…where 𝜌 the density of wood substances (1.5 g/cm 3 ); 𝜌 -density of wood and solid fraction of charcoal (Kellogg and Wangaard, 1969;Mania et al, 2023). The density of wood waste and solid wood waste charcoal is calculated by dividing the mass of a sample by its volume.…”
Section: Fig 24 Charcoal Samples After Carbonisation (Made By the Aut...mentioning
confidence: 99%